OsCYP21-4, a novel Golgi-resident cyclophilin, increases oxidative stress tolerance in rice - Lee, Sang S.; Park, Hyun J.; Jung, Won Y.; Lee, Areum; Yoon, Dae H.; You, Young N.; Kim, Hyun-Soon; Kim, Beom-Gi; Ahn, Jun C.; Cho, Hye S. (Frontiers in Plant Science, 2015)
OsCYP21-4 is a rice cyclophilin protein that binds to cyclosporine A, an immunosuppressant drug. CYP21-4s in Arabidopsis and rice were previously shown to function as mitochondrial cyclophilins, as determined by TargetP analysis. In the current study, we found that OsCYP21-4-GFP localized to the Golgi, rather than mitochondria, in Nicotiana benthamiana leaves, which was confirmed based on its co-localization with cis Golgi α-ManI-mCherry protein. OsCYP21-4 transcript levels increased in response to treatments with various abiotic stresses and the phytohormone abscisic acid, revealing its stress-responsiveness. CYP21-4 homologs do not possess key peptidyl prolyl cis/trans isomerase (PPIase) activity/cyclosporine A (CsA) binding residues, and recombinant OsCYP21-4 protein did not convert the synthetic substrate Suc-AAPF-pNA via cis- trans- isomerization in vitro. In addition, transgenic plants overexpressing OsCYP21-4 exhibited increased tolerance to salinity and hydrogen peroxide treatment, along with increased peroxidase activity. These results demonstrate that OsCYP21-4 is a novel Golgi-localized cyclophilin that plays a role in oxidative stress tolerance, possibly by regulating peroxidase activity.